Coronary flow reserve in the contralateral artery increases after successful coronary angioplasty in patients with spontaneously visible collateral vessels. Issue 5 (1st November 1998) - Kyriakides, Z S; Antoniadis, A; Kolettis, T M; Kremastinos, D T
Abstract : Objective: To test the hypothesis that coronary flow reserve could increase in the angiographically normal contralateral artery after successful coronary angioplasty of an ipsilateral coronary artery. Design: Coronary flow reserve was estimated using a Doppler flow guide wire, by giving intracoronary adenosine in the contralateral artery, before and 15 minutes after the end of angioplasty. Setting: Tertiary referral centre. Patients: 31 patients, mean (SD) age 56 (11) years, with stable angina and single vessel disease, undergoing angioplasty of the right coronary or the left anterior descending artery. Results: In the contralateral artery baseline average peak velocity was 21 (9) cm/s before angioplasty and decreased to 12 (6) cm/s after (p < 0.005), while hyperaemic average peak velocity was 47 (19) cm/s before and decreased to 34 (15) cm/s after (p < 0.005). However, coronary flow reserve in the contralateral artery was 2.4 (0.7) before angioplasty and increased to 2.9 (0.6) after (p < 0.05). The contralateral coronary flow reserve after angioplasty increased by 0.8 (0.4) in 11 patients with visible collaterals before angioplasty and by 0.3 (0.6) in the remaining patients without visible collaterals (p < 0.05). Blood pressure and heart rate were unchanged after the procedure. Conclusions: Coronary flow reserve in an angiographically normal contralateral artery increases after successful coronary angioplasty of the ipsilateral artery in patients with spontaneously visible collateral vessels before the procedure.